PENGARUH METODE SOSIALISASI ORANGTUA DAN KONTROL DIRI TERHADAP KARAKTER SOPAN SANTUN REMAJA - Wardah, Farhatil; Hastuti, Dwi; Krisnatuti, Diah (Jurnal Pendidikan Karakter, 2019)
Adolescent is a transition period with developmental tasks of gaining a social role and emotional freedom from parents, but adolescent still cannot control themselves well. This study examines gender differences between boys and girls in parents socialization method, self control and their influence on manners character of adolescence. This study used a cross-sectional research design. A diverse sample of junior high school students (n=187; 87 boys and 100 girls) were selected considering proportionate random sampling method to answer survey using questionnaires. The collected data was analyzed by SPSS 16.0. Findings of this study suggest that parents socialization method (Ï = 0.323) and self control (Ï=0.401) have positive effects on manners character of adolescence.